Automotive engines theory and servicing - Halderman, James D. 1943- (Prentice Hall, 1997)
Presenting the principles and practices of engine rebuilding, engine theory and in-the-vehicle service in a concise format, this text makes clear connections between theory and servicing, opening coverage with technical material, then moving into diagnosis, troubleshooting, and service procedures. This edition has been updated and streamlined to reflect the latest information in the field, including new information on the aluminium V-8s, V-6s and 4-cylinder engines. It also includes complete diagnosis, operation and engine machining information for technicians wishing to take the National Institute of Automotive Service Excellence (ASE) tests.